Type 1 hypersensitivity from vitamin B12 injection: a case report - Khatrawi, Elham Mohammed; Prajjwal, Priyadarshi; Ranjan, Raunak (International Journal of Research in Medical Sciences, 2022)
Vitamin B12 is essential for the development of healthy nerves and red blood cells. Vitamin B12 deficiency is becoming widespread and most commonly affects the elderly, pregnant women, vegetarians, and patients with renal or intestinal diseases. Either parenteral vitamin B12 treatment or high-dose oral vitamin B12 treatment is an effective therapy regardless of etiology. Parenteral therapy using the intramuscular route is considered the most familiar treatment for vitamin B12 deficiency. Anaphylactic reaction after intramuscular injection is an uncommon and potentially serious side effect. In this study, we are documenting a case of anaphylactic reaction in a 50-year-old man after her second dose of intramuscular injection of cyanocobalamin. The purpose of this case report is to highlight the need to understand the rare life-threatening side effect of intramuscular cyanocobalamin. Health care providers should be vigilant while administering the intramuscular injection of cyanocobalamin to vitamin B12 deficient patients.